2022
DOI: 10.1111/ijlh.13904
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial involvement in a common B‐cell acute lymphoblastic leukemia patient

Abstract: A 66-year-old male with 6 months history of acute lymphoblastic leukemia (ALL) present to the outpatient for the follow up. The peripheral blood and bone marrow (Figure 1A) smear show no abnormal cell. But the pericardial fluid was found by the ultrasound by routine examination, pericardiocentesis was performed and a large number of lymphocytic leukemia like blast was found in the pericardial effusion (Figure 1B). Furthermore, these abnormal B cells (85.2%) were confirmed by the flow cytometry, with the phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Pleural fluid occurrence is more frequent in T-lymphoblastic leukemia/lymphoma, followed by AML. He, et al [8] reported a male patient diagnosed as having B-cell acute lymphoblastic leukemia, in whom pericardial effusion was incidentally discovered during follow-up.…”
Section: Sonal Information Was Not Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleural fluid occurrence is more frequent in T-lymphoblastic leukemia/lymphoma, followed by AML. He, et al [8] reported a male patient diagnosed as having B-cell acute lymphoblastic leukemia, in whom pericardial effusion was incidentally discovered during follow-up.…”
Section: Sonal Information Was Not Includedmentioning
confidence: 99%
“…He, et al . [ 8 ] reported a male patient diagnosed as having B-cell acute lymphoblastic leukemia, in whom pericardial effusion was incidentally discovered during follow-up.…”
mentioning
confidence: 99%